Promiscuous pollinators—Evidence from an Afromontane sunbird–plant pollen transport network. (22nd May 2019) - Nsor, Charles A.; Godsoe, William; Chapman, Hazel M.
Abstract: Sunbirds play a major role in the pollination of Old World nectivorous plants. However, with the exception of the Cape Floristic Region there is a major knowledge gap around African nectivore interaction networks—a stark contrast from the abundance of neotropical hummingbird–plant networks. Here, we describe a sunbird pollen transfer network (PTN) which we use in conjunction with a sunbird flower visitation network (FVN) to explore levels of sunbird specialization within an Afromontane forest habitat. Both networks were generalized compared with similar‐sized hummingbird networks, reflecting the wide range of flower types visited, the generalist diet, and bill characteristics of sunbirds. Three sunbird species from the genus Cinnyris accounted for 85% of flower visits and 77% of all pollen transported. Of the 17 plant species across both networks, 15 are predominantly pollinated by insects while Anthonotha noldeae (Fabaceae–Caesalpinioideae) and Globimetula braunii (Loranthaceae) depend on sunbirds for seed set. Sunbird species average bill lengths varied between 14.5 mm (the variable sunbird) and 23.6 mm (the Green‐headed Sunbird), but, while more pollen was carried on longer bills, we found no evidence for a relationship between bill length and type of flower visited. Both networks were nested. Some specialization was observed in both networks although this does not appear to be driven much by sunbird–flower trait matching. Overall, our results suggest that in contrast to nectivores elsewhere, factors such as phenology and/or environment, rather than morphology, may play important roles in limiting potential sunbird–flower interactions and need further investigation.